UMA AVALIAÇÃO POLÍTICA DO PRONASCI À LUZ DA CIDADANIA NO ESTADO DEMOCRÁTICO DE DIREITO BRASILEIRO. - JESUS, Thiago Allisson Cardoso de (2012)
Policy Evaluation of the National Program of Public Security and Citizenship. Analyzes the phenomenon of violence based on various theoretical constructs as well as its causes, impacts and importance of control mechanisms, assuming the legitimate monopoly of force by the State and its protective purpose. Traverses the path of security policies to the current public security policy. Investigates the recognition of the fundamental right to the public safety. Discusses it as a policy that combines Methodologically, it uses a literature review through a literature research, analysis of documents and data related to the Program and to the activities developed to achieve public safety. Evaluates if the conceptions of citizenship aims to maintain or change the order. Asks about the political priorities of the State regarding the application of resources. Reflects if PRONASCI meets the constitutional sense of protection to the human person and if favors a committed participation of civil society in collaboration with the government and questioned his motives. Discusses the rationalities, interests and expectations that guided the development of this policy and encourages the production of scientific knowledge to the build of an environment for discussion and for incentive further studies and reflections on the management and construction of the Brazilian res publica.